2010
DOI: 10.1890/08-1446.1
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of native shrubs on Bromus tectorum demography

Abstract: There is increasing recognition that overall interactions among plant species are often the net result of both positive and negative effects. However, the positive influence of other plants has rarely been examined using detailed demographic methods, which are useful for partitioning net effects at the population level into positive and/or negative effects on individual vital rates. This study examines the influence of microhabitats created by the native shrubs Artemisia tridentata and Purshia tridentata on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 68 publications
(64 reference statements)
0
67
1
Order By: Relevance
“…We found little evidence of a seedbank that lasts for >1 year. Studies in other invaded areas have found a similar lack of dormancy over multiple years in B. tectorum seeds (Hulbert 1955;Griffith 2010), although some studies have found Table 2 Results of linear mixed-effects models of demographic measurements of Bromus tectorum and aboveground biomass of neighboring plants in response to precipitation treatments a a Only predictor variables that accounted for significant variation in the response variables were included in final analyses. All treatment estimates are compared to the control treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found little evidence of a seedbank that lasts for >1 year. Studies in other invaded areas have found a similar lack of dormancy over multiple years in B. tectorum seeds (Hulbert 1955;Griffith 2010), although some studies have found Table 2 Results of linear mixed-effects models of demographic measurements of Bromus tectorum and aboveground biomass of neighboring plants in response to precipitation treatments a a Only predictor variables that accounted for significant variation in the response variables were included in final analyses. All treatment estimates are compared to the control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Competition from resident species can affect resource availability and contribute to the invasion resistance of ecosystems (e.g., Tilman 1997;Naeem et al 2000;Corbin and D'Antonio 2004). Competition from established species may limit the ability of new species to invade (Kennedy et al 2002) or, alternatively, neighboring plant species may have no effect, or even facilitate the establishment of new species (Bulleri et al 2008;Griffith 2010). The outcomes of interactions between species may also shift under a changing climate (Dormann 2007;Concilio et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Population growth of B. tectorum is strongly sensitive to rates of seedling germination and establishment, more so than to any other life history transition (Griffith 2010). Thus, the timing of emergence for this annual grass may be absolutely critical for invasive success, and can represent a strong mortality filter.…”
Section: Emergencementioning
confidence: 99%
“…particular functional traits), but this contributes to an overall 'jack-of-alltrades' result with less variability across environments in terms of population-level consequences (Richards et al 2006). For an annual species like B. tectorum, biomass is tightly linked to lifetime seed production (Griffith 2010), and plasticity in function that helps to maintain biomass accumulation is likely to be important.…”
Section: Morphology and Growthmentioning
confidence: 99%
“…In contrast, L. argenteus had a weak, non-significant inhibitory effect on Bromus emergence. Other field studies investigating the effects of mature herbaceous vegetation on Bromus emergence have found both positive and negative effects (Chambers et al 2007;Griffith 2010). Emergence differed among species with Bromus having the highest overall percentage of seeds emerge (59%) followed by Elymus (54%) and Eriogonum (32%).…”
Section: Discussionmentioning
confidence: 95%